Isolation, Identification and Pigment Analysis of Novel Cyanobacterial Strains from Thermal Springs - Sandugash K. Sandybayeva; Bekzhan D. Kossalbayev; Bolatkhan K. Zayadan; Jiří Kopecký; Ardak B. Kakimova; Kenzhegul Bolatkhan; Suleyman I. Allakhverdiev (Plants)
Cyanobacterial pigments have attracted considerable attention in industry due to their bioactive potential and natural origin. In the present study, the growth dynamics and pigment composition, in terms of chlorophyll a, total carotenoids and phycobiliprotein content, of four cyanobacterial strains isolated from thermal springs, namely Oscillatoria subbrevis CZS 2201, Phormidium ambiguum CZS 2205, Nostoc calcicola TSZ 2203, and Synechococcus sp. CZS 2204, were investigated. The analysis revealed that the maximum quantity of chlorophyll a and total carotenoids was observed in Oscillatoria subbrevis CZS 2201 (26.49 and 3.44 µg mL−1), followed by Phormidium ambiguum CZS 2205 (18.64 and 2.32 µg mL−1), whereas a minimum amount was detected in Synechococcus sp. CZS 2204 (12.13 and 1.24 µg mL−1), respectively. In addition, Oscillatoria subbrevis CZS 2201 showed higher quantity of phycobiliproteins, especially C-phycocyanin (45.81 mg g−1), C-phycoerythrin (64.17 mg g−1) and C-allophycocyanin (27.45 mg g−1). Moreover, carotenoid derivatives of Oscillatoria subbrevis CZS 2201 were also identified, among which β-carotene was the dominant form (1.94 µg mL−1), while the accumulation of zeaxanthin and myxoxanthophyll was relatively high (0.53 and 0.41 µg mL−1, respectively) compared with echinenone and cryptoxanthin (0.34 and 0.23 µg mL−1, respectively). The study revealed that Oscillatoria subbrevis CZS 2201 was a potent producer of secondary carotenoids, including myxoxanthophyll.